Autonomous Drift Cornering with Mixed Open-loop and Closed-loop Control. Issue 1 (July 2017) - Zhang, F.; Gonzales, J.; Li, K.; Borrelli, F.
Abstract: Expert drivers have the skill to perform high side slip maneuvers, like drifting, during racing events to minimize lap time. Due to the complex dynamics of these maneuvers, transient drift is difficult to model and to control in autonomous vehicles. In this paper, the authors present a mixed open-loop and closed-loop control strategy to perform a transient drift-corning trajectory. The reference trajectory is generated from a ruled-based algorithm. We validate the planning and control techniques in simulation using Simulink/Carsim, and experimentally using an open source, low cost 1/10 scale RC car.